Digital watermarking - Petitcolas Fabien A P ed.; International Workshop, IWDW 2002 on Digital Watermarking (21-22 Nov 2002 : Seoul,Korea); International workshop, IWDW 2002 on digital watermarking Seoul, Korea 21-22 Nov 2002 (Berlin Springer-Verlag, 2003)
This book presents 21 selected papers which are organized in topical sections on fundamentals, new algorithms, watermarking unusual content, fragile watermarking, robust watermarking, and adaptive watermarking.The theme of the papers highlight the subsequent topics:Data compression, Digital rights protection, Digital watermarking, Image authentication, Image watermarking, Information hiding, Intellectual property protection, Multimedia authentication, Steganography, Video watermarking and Water marking algorithms.
Keywords: Digital watermarking; Watermarking-computer applications